Volume 2A: Turbomachinery 2018
DOI: 10.1115/gt2018-75153
|View full text |Cite
|
Sign up to set email alerts
|

Stall Inception in Low Pressure Ratio Fans

Abstract: A combined experimental and computational test programme, with two low pressure ratio aero-engine fans, has been used to identify the flow mechanisms at stall inception and the subsequent stall cell growth. The two fans have the same rotor tip clearance, annulus design and downstream stators, but different levels of tip loading. The measurement data show that both fans stall via spike-type inception, but that the growth of the stall cell, and the final cell size, is different in each fan. The computations, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
(8 reference statements)
2
21
0
Order By: Relevance
“…Decreasing the negative axial momentum flux in the leakage flow increased stable operating range until stall initiated through the passage separation mechanism. Kim, et al (2019) observed a similar distinction in inception mechanism for two low speed fan designs. Supersonic flow at the tip produced suction surface boundary layer separation downstream of the shock, contrasting the corner separation in the subsonic cases.…”
Section: Fan and Compressor Stall With Distorted Inflowmentioning
confidence: 55%
See 3 more Smart Citations
“…Decreasing the negative axial momentum flux in the leakage flow increased stable operating range until stall initiated through the passage separation mechanism. Kim, et al (2019) observed a similar distinction in inception mechanism for two low speed fan designs. Supersonic flow at the tip produced suction surface boundary layer separation downstream of the shock, contrasting the corner separation in the subsonic cases.…”
Section: Fan and Compressor Stall With Distorted Inflowmentioning
confidence: 55%
“…values for wall cells were kept below 5 everywhere other than near stagnation points. Solver settings mirrored those calibrated and validated by Kim, et al (2019) for Fan A with clean inflow. Jameson's dual time-stepping method (Jameson, 1991) gave unsteady calculations second order accuracy in time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct numerical simulation (DNS), large eddy simulation (LES), and hybrid RANS/LES have been demonstrated to yield much more accurate results (You et al, 2007;Decaix et al, 2015;Scillitoe et al, 2017;Liu et al, 2017;Yan et al, 2018). Higher fidelity methods could be used to study turbulence physics and to educate RANS turbulence modelling (Liu et al, 2011;Lee et al, 2018;Kim et al, 2018;Tang et al, 2018). LES is a favorite and powerful tool for turbulence research because of much higher resolution compared with hybrid RANS/LES and much lower cost compared with DNS.…”
Section: Introductionmentioning
confidence: 99%